2012
DOI: 10.1016/j.jacc.2012.01.063
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiologic Remodeling of the Left Ventricle in Pressure Overload-Induced Right Ventricular Failure

Abstract: Pressure-induced RVF is associated with electrophysiologic remodeling of the atrophic LV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
36
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 39 publications
3
36
0
1
Order By: Relevance
“…Chronically elevated RV afterload, RV dysfunction, and lung hyperinflation result in relative underfilling of the left ventricle in advanced lung disease. Animal models and human case series have demonstrated that, in response to a chronically reduced LV preload, there is a decrease in the LV myocyte cross-sectional area, a prolongation of LV action potential, and a decrease in the calcium-ATPase pump involved in myocyte relaxation, resulting in impaired LV relaxation and diminished compliance (16,19,(21)(22)(23)(24)45). In addition, the left ventricle's ability to relax may be further impaired perioperatively by the release of proinflammatory cytokines in PGD, including IL-6, which leads to a reduction in sarcoplasmic reticulum Ca 21 -ATPase (46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Chronically elevated RV afterload, RV dysfunction, and lung hyperinflation result in relative underfilling of the left ventricle in advanced lung disease. Animal models and human case series have demonstrated that, in response to a chronically reduced LV preload, there is a decrease in the LV myocyte cross-sectional area, a prolongation of LV action potential, and a decrease in the calcium-ATPase pump involved in myocyte relaxation, resulting in impaired LV relaxation and diminished compliance (16,19,(21)(22)(23)(24)45). In addition, the left ventricle's ability to relax may be further impaired perioperatively by the release of proinflammatory cytokines in PGD, including IL-6, which leads to a reduction in sarcoplasmic reticulum Ca 21 -ATPase (46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the left ventricle's ability to relax may be further impaired perioperatively by the release of proinflammatory cytokines in PGD, including IL-6, which leads to a reduction in sarcoplasmic reticulum Ca 21 -ATPase (46)(47)(48). The left ventricle appears to undergo reverse remodeling following restoration of preload over time; however, this adaptation is not immediate, and abnormal filling may persist up to 1 year after transplant (16,23,(49)(50)(51)(52)(53)(54). Therefore, it is possible that acute and chronic impairment in LV diastolic function may contribute to pulmonary edema and PGD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Synchronicity is an important factor for the construction of a transplantable artificial organ, since asynchronous regions impair the contractility, as well as potentially increase the risk of lethal cardiac arrhythmias. The calculated CV in our engineered heart tissues was markedly decreased (approximately 5 cm/s) as compared to that reported previously in an adult rat heart [22,23] or in an in vitro cultured neonatal rat cardiomyocyte (NRCM), whereas it was similar to that of NRCM with Cx43 mutation [24]. Slow conduction and electrical instability were more apparent in the whole heart.…”
Section: Discussionmentioning
confidence: 40%